Dependable wireless communications for vehicular networks - Almeida, João Miguel Pereira de (2018)
Vehicular communications are a promising field of research, with numerous potential services that can enhance traffic experience. Road safety is the most important objective behind the development of wireless vehicular networks, since many of the current accidents and fatalities could be avoided if vehicles had the ability to share information among them, with the road-side infrastructure and other road users. A future with safe, efficient and comfortable road transportation systems is envisaged by the different traffic stakeholders - users, manufacturers, road operators and public authorities. Cooperative Intelligent Transportation Systems (ITS) applications will contribute to achieve this goal, as well as other technological progress, such as automated driving or improved road infrastructure based on advanced sensoring and the Internet of Things (IoT) paradigm. Despite these significant benefits, the design of vehicular communications systems poses difficult challenges, mainly due to the very dynamic environments in which they operate. In order to attain the safety-critical requirements involved in this type of scenarios, careful planning is necessary, so that a trustworthy behaviour of the system can be achieved. Dependability and real-time systems concepts provide essential tools to handle this challenging task of enabling determinism and fault-tolerance in vehicular networks. This thesis aims to address some of these issues by proposing architectures and implementing mechanisms that improve the dependability levels of realtime vehicular communications. The developed strategies always try to preserve the required system’s flexibity, a fundamental property in such unpredictable scenarios, where unexpected events may occur and force the system to quickly adapt to the new circumnstances.The core contribution of this thesis focuses on the design of a fault-tolerant architecture for infrastructure-based vehicular networks. It encompasses a set of mechanisms that allow error detection and fault-tolerant behaviour both in the mobile and static nodes of the network. Road-side infrastructure plays a key role in this context, since it provides the support for coordinating all communications taking place in the wireless medium. Furthermore, it is also responsible for admission control policies and exchanging information with the backbone network. The proposed methods rely on a deterministic medium access control (MAC) protocol that provides real-time guarantees in wireless channel access, ensuring that communications take place before a given deadline. However, the presented solutions are generic and can be easily adapted to other protocols and wireless technologies. Interference mitigation techniques, mechanisms to enforce fail-silent behaviour and redundancy schemes are introduced in this work, so that vehicular communications systems may present higher dependability levels. In addition to this, all of these methods are included in the design of vehicular network components, guaranteeing that the real-time constraints are still fulfilled. In conclusion, wireless vehicular networks hold the potential to drastically improve road safety. However, these systems should present dependable behaviour in order to reliably prevent the occurrence of catastrophic events under all possible traffic scenarios.